Impact of social media advertising on consumer behavior: role of credibility, perceived authenticity, and sustainability - Kothari, Hemant; Choudhary, Avinash; Jain, Apurva; Singh, Shivoham; Prasad, K. D. V.; Vani, U. K. (Frontiers in Communication, 2025)
IntroductionSocial media advertising is a crucial factor for predicting consumer behavior. Further credibility, authenticity, and sustainability of social postings enhance consumer purchase intentions in general and online shopping in particular. This empirical study investigated the impact of social media advertising on consumer behavior and the role of credibility, perceived authenticity and sustainability. The study also investigated the mediating effect of trust in the relationship between social media advertising and consumer behavior.MethodsTo measure the impact of the social media advertising effect on consumer behavior, eight reflective constructs, namely, credibility, sustainability, perceived authenticity, social media advertising effectiveness, satisfaction, purchase intentions and perceived value, were assessed. For the mediation analysis, consumer behavior was modeled as a higher-order construct with three sub-dimensions: satisfaction, perceived value and purchase intentions. Furthermore, the construct social media effectiveness is also modeled as a higher-order construct with four sub-dimensions: credibility, sustainability, authenticity and social media advertisement effectiveness. The data were collected from active social media users who engage in brand advertising and online shopping. A total of 500 valid responses were subjected to exploratory and confirmatory factor analysis, and the hypotheses were tested via structural equation modeling.Results and discussionThe SEM results reveal that constructs credibility and sustainability are strong predictors of consumer behavior in the context of social media advertising effectiveness. The mediating variable of trust partially mediated the relationship between social media effectiveness and consumer behavior. The outcome has several practical theoretical implications for industry. The brand managers should identify that consumer trust and engagement are not only by-products of risk but also actively cultivated through strategic advertising efforts. To maximize the effectiveness of their social media campaigns, brands should focus on building reliability through transparency, enhancing authenticity through reliable storytelling and promoting sustainability with real commitment.